Complete CAE Workbook without answers - Matthews L. Laura (Cambridge, Cambridge University Press, 2010)
Complete CAE is a brand new course for the CAE exam. It combines the very best in contemporary classroom practice with stimulating topics aimed at mature teenagers and young adults. The course covers every part of the CAE exam in detail providing preparation, practice, information and advice to ensure that students are fully prepared for every part of the exam. Informed by Cambridge's unique searchable database of real exam papers, the Cambridge Learner Corpus*, and providing a complete CAE exam paper specially prepared by Cambridge ESOL, Complete CAE is the most authentic CAE exam preparation course available. Complete CAE Workbook without answers with Audio CD: contains 14 topic-based units for homework and self-study, each unit providing full exam practice in one part of the CAE Reading Paper or in two parts of the CAE Use of English Paper provides full exam practice in each unit for one part of the CAE Listening Paper, offers further practice in the grammar and vocabulary taught in the Student's Book, contains exercises for the development of essential writing skills such as paragraph organisation, self-correction, spelling and punctuation based on the results from the.